2001
DOI: 10.1116/1.1414120
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy of interfaces by infrared–visible sum frequency generation

Abstract: During the past decade vibrational sum frequency generation as a method to study interfaces has matured and can now be applied more routinely to systems of increasing complexity. The article provides a brief overview of technical aspects of infrared–visible sum frequency generation, compares this nonlinear technique with its linear analogs, and highlights the latest applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
294
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(301 citation statements)
references
References 257 publications
7
294
0
Order By: Relevance
“…In this context, nonlinear vibrational sum frequency generation (VSFG) spectroscopy offers the needed inherent surface specificity on the nanolayer scale. The method, which has already found numerous applications in various areas such as surface dynamics and catalysis [Buck and Himmelhaus, 2001;Lambert et al, 2005], spectroscopy of air-aqueous interfaces , and for the examination of environmental and biomolecular surfaces [Geiger, 2009;Yatawara et al, 2009], was recently shown by us to be suitable for investigating natural sea surface nanolayers as well [Laß et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, nonlinear vibrational sum frequency generation (VSFG) spectroscopy offers the needed inherent surface specificity on the nanolayer scale. The method, which has already found numerous applications in various areas such as surface dynamics and catalysis [Buck and Himmelhaus, 2001;Lambert et al, 2005], spectroscopy of air-aqueous interfaces , and for the examination of environmental and biomolecular surfaces [Geiger, 2009;Yatawara et al, 2009], was recently shown by us to be suitable for investigating natural sea surface nanolayers as well [Laß et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that in many cases the generated SFG signal intensity simply depends on the square of the secondorder susceptibility (Buck and Himmelhaus 2001). χ (2) can be interpreted as a macroscopic average of the probed molecular hyperpolarizabilities β such that the overall SFG intensity is proportional to the number density of SFG active surface oscillators N squared:…”
Section: Introductionmentioning
confidence: 99%
“…In principle, these limitations can be overcome by sensitive detection methods that are limited to a well-defined layer by their inherent physical properties. A very promising method that already has led to important findings in various fields of basic research, such as surface catalysis and liquid-gas interface sciences, is the so-called infrared-visible or vibrational sum-frequency generation spectroscopy (IV-SFG, VSFG) (Buck and Himmelhaus 2001;Lambert et al 2005). The method has found first applications in environmental sciences as well (Geiger 2009).…”
mentioning
confidence: 99%
“…1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25 To simply put it, SHG is the second order nonlinear process where two photons with the same fundamental frequency (ω) interact with a nonlinear medium simultaneously to generate a photon with the second harmonic frequency (2ω). If the two fundamental frequencies are not the same, a photon at the sum of these two frequencies can be generated from the so-called SFG process.…”
Section: Introductionmentioning
confidence: 99%